The SISTEM INFORMASI PENGELOLAAN DAN PENCATATAN KAS KECIL PADA CV. MULIA FROZINDO BERBASIS APLIKASI WEB ACCOUNTING - citra (Transpublika Publisher, 2021)
Petty cash has a vital part in the exercises/functional exercises of the organization. Trivial money is typically utilized in overseeing generally little ostensible exchanges that happen each day. The object of this exploration is CV. Mulia Frozindo, which is one of the companies engaged in the design, supply, install, and maintenance of frozen facilities/coolants. In cash management and accounting records, especially for petty cash funds in CV. Mulia Frozindo is still handled by one section, namely the admin section. With so much transaction data that occurs, if the information assortment is done physically, a ton of time is squandered on monetary information handling in light of the fact that there are numerous stages that should be finished. The resulting information isn't really exact and proper. That way the web accounting application has been created to make it easier to make decisions on the business being run. The use of web accounting applications is very efficient and effective for an entrepreneur in running his business. Financial data processing, which only inputs transaction data, can produce the desired reports for decision making.